THIRSTY FOR FRUCTOSE: Arginine Vasopressin, Fructose, and the Pathogenesis of Metabolic and Renal Disease - Student, Jeffrey; Sowers, James; Lockette, Warren (Frontiers in Cardiovascular Medicine, 2022)
We review the pathways by which arginine vasopressin (AVP) and hydration influence the sequelae of the metabolic syndrome induced by high fructose consumption. AVP and inadequate hydration have been shown to worsen the severity of two phenotypes associated with metabolic syndrome induced by high fructose intake–enhanced lipogenesis and insulin resistance. These findings have implications for those who frequently consume sweeteners such as high fructose corn syrup (HFCS). Patients with metabolic syndrome are at higher risk for microalbuminuria and/or chronic kidney disease; however, it is difficult to discriminate the detrimental renal effects of the metabolic syndrome from those of hypertension, impaired glucose metabolism, and obesity. It is not surprising the prevalence of chronic renal insufficiency is growing hand in hand with obesity, insulin resistance, and metabolic syndrome in those who consume large amounts of fructose. Higher AVP levels and low hydration status worsen the renal insufficiency found in patients with metabolic syndrome. This inter-relationship has public health consequences, especially among underserved populations who perform physical labor in environments that place them at risk for dehydration. MesoAmerican endemic nephropathy is a type of chronic kidney disease highly prevalent in hot ambient climates from southwest Mexico through Latin America. There is growing evidence that this public health crisis is being spurred by greater fructose consumption in the face of dehydration and increased dehydration-dependent vasopressin secretion. Work is needed at unraveling the mechanism(s) by which fructose consumption and increased AVP levels can worsen the renal disease associated with components of the metabolic syndrome.